Jesus the Mediator - Brownsberger, William (Book collections on Project MUSE., 2013)
"In Jesus the Mediator, William L. Brownsberger offers an account of the human psychology assumed by the Second Person of the Trinity in light of its salvific significance. Instead of focusing directly on classical understandings of how salvation is accomplished, this book draws attention to the Person and human nature that soteriology must presuppose. The book follows a classical psychological taxonomy (intellect, will, sensitive appetites) of human nature, presupposing a traditional articulation of the hypostatic union as background for this reflection. The book begins by considering Christ's human intellect. The distinct, but complementary, perspectives of Maurice Blondel and St. Thomas are combined to argue in favor of a Christological maximalism regarding the extent of Jesus' human knowledge from the character of his saving mission. This is followed by a two-part reflection on the gulf between finite and infinite being that is bridged by the mediator. In this vein, one chapter focuses on Christ's active mediatorship in voluntary action, while another approaches the integration of the finite and Infinite in his personal constitution. The final chapter treats Jesus' anger as suggestive of the role that his emotional life plays in salvation. Brownsberger supports the main theses of St. Thomas's Christology, while also providing key insights from the philosophical tradition of the past two centuries and from the Christological debates of the 1940s - 1960s. Many of the discoveries of the latter became obsolete in the post-conciliar shift in theological emphases before they could be developed and applied. By means of such insights, the author seeks to draw the identity of Jesus Christ into a tight, organic unity with his redemptive mission of mediation."--Publisher's website.